Understanding the Incidence of T2DM Following Gestational Diabetes Mellitus: A Comprehensive Systematic Review - Yusuf, Lydia; Sylvia (International Medical Journal Corp. Ltd, 2024)
Background: Gestational Diabetes Mellitus (GDM) is a common metabolic issue in pregnancy, marked by high plasma glucose levels first detected during pregnancy. Research shows that women with GDM have at least a seven-fold higher risk of developing T2DM compared to those with normal pregnancies. This study aims to serve a comprehensive systematic review to analyze the incidence rate of T2DM after GDM in literatures of the last 10 years. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, ten articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Postpartum care and long-term monitoring for women with gestational diabetes mellitus (GDM) are essential due to the increased risk of type 2 diabetes mellitus (T2DM). Future research should target modifiable risk factors and enhance postpartum screening to mitigate associated health risks.